Enhancing the hydrogen transfer catalytic activity of hybrid carbon nanotube-based NHC–iridium catalysts by increasing the oxidation degree of the nanosupport. Issue 14 (7th April 2016) - Blanco, Matías; Álvarez, Patricia; Blanco, Clara; Jiménez, M. Victoria; Pérez-Torrente, Jesús J.; Oro, Luis A.; Blasco, Javier; Cuartero, Vera; Menéndez, Rosa
Abstract : Oxidation of the support increase the HT catalytic activity. Abstract : CVD-grown multiwalled carbon nanotubes were purified by applying four different treatments with increasing oxidation severity. The growing severity of the treatment results in progressive oxygen functionalization of the surface along with introduction of an increasing quantity of defects on the carbon nanotube walls. Iridium– N -heterocyclic carbene complexes were covalently anchored to those oxidized surfaces through their surface carboxylic acids via acetyl linkers. The carbon nanotube-based iridium–NHC hybrid materials developed are active in the hydrogen-transfer reduction of cyclohexanone to cyclohexanol with 2-propanol/KOH as hydrogen source but with rather different activity. The catalytic activity of the hybrid catalysts is strongly influenced by the type and amount of oxygenated functionalization resulting from the treatment applied to the support, being the most active and the most oxidized material.